(معاني العفو عند القدرة في الشعرِ الأندلسـي من الفتحِ حتى عصر المرابطين) (92-555هـ /710- 1160م) - عبد علي محيي, انتظـار (Al-Adab Journal, 2018)
1.The research is based on good collection of Andalusian poetic texts about the poetry of amnesty when there is power that was mixed with other purposes. As we find, there are many poets who organized the poetry in more than one poem, such as " Al-Mutamad " and his son Al-Radi and Ibn Zaydun, as their numbers approached to twelve poets. This number, of course, will not be the last one, a number allowed by research and investigation2.Adversity and setbacks is one of the reasons for the appearance of this purpose, and its content is the same from one era to another owing to similarities of circumstances and suffering. , Andalusian poetry was full of this meaning. .The Amnesty poetry in power is of great importance as a container for a vital human subject in which the shepherds express the most important humanitarian experience in the face of adversity and calamity. 4 - These poems are characterized that they have the ability to deliver and interact with the listener, and make him change his mind and exposure of his intensity and joy of his survival penalty of death.The texts in this regard indicate the similarity of the human emotions of the Andalusian poets and attitudes towards the joy between the public and the private in terms of winning pardons and getting rid of the hardships after these hardships began to be difficult, but ended with a happy ending which led to the joy of amnesty.6.The poetry of amnesty is not confined to the general poets in Andalusia, but also to their senior and famous ones.7 - The texts were of a great importance, because it represents a historical document leads us to identify the events and political figures, religious and social that prevailed in the society in that era, because it reflects a position sees the self and the other from the perspective of Astalai, and amnesty to distinguish each other. 8 - This poetic style indicates the nature of Andalusians leaning towards renewal, and non - compliance with the previous substantive rules. 9 - The poetry of amnesty at the first ability to be the most poetic purposes are serious, as the poets can win the pardon after the despair , these poems folds a difficult phase of their lives, which was the systems of these poems, which were in fact only the equivalent of the substantive life, they got the Poets to the end of joyousness .10 - Not all the poets who organized this subject were rewarded with amnesty, and rejoiced later, but some of them suffered from humiliation in a long prison that does not end, and some of them died, but most of the poems that organized achieved amnesty.It is clear that the Andalusians are very interested in poetry, and not to abandon it in all matters of life, but such poetry did not leave them in most severe trials and fatalities and cruelty to man.Political events have had their role in the emergence of this poetic art, because it stems from the core of a tragedy of Andalusia, which had no precedent in the history of Islam.Through these poems, it is important to express the importance of poetry in the expression of issues of great importance to the life of the Andalusian ArabsThe Andalusian poets singled out the amnesty with much care, in terms of choosing the suitable sea for their subjects, choosing the Arabic rhetoric, and decorating the speech with exquisite colors of words15.Andalusia was not the first to this purpose as well as the many texts were in the era of the kings of " Tawaif" , we found many poetic texts in the East.